The α and Δ isoforms of CREB1 are required to maintain normal pulmonary vascular resistance. - Lili Li (Public Library of Science (PLoS), 2013)
Chronic hypoxia causes pulmonary hypertension associated with structural alterations in pulmonary vessels and sustained vasoconstriction. The transcriptional mechanisms responsible for these distinctive changes are unclear. We have previously reported that CREB1 is activated in the lung in response to alveolar hypoxia but not in other organs. To directly investigate the role of α and Δ isoforms of CREB1 in the regulation of pulmonary vascular resistance we examined the responses of mice in which these isoforms of CREB1 had been inactivated by gene mutation, leaving only the β isoform intact (CREB(αΔ) mice). Here we report that expression of CREB regulated genes was altered in the lungs of CREB(αΔ) mice. CREB(αΔ) mice had greater pulmonary vascular resistance than wild types, both basally in normoxia and following exposure to hypoxic conditions for three weeks. There was no difference in rho kinase mediated vasoconstriction between CREB(αΔ) and wild type mice. Stereological analysis of pulmonary vascular structure showed characteristic wall thickening and lumen reduction in hypoxic wild-type mice, with similar changes observed in CREB(αΔ). CREB(αΔ) mice had larger lungs with reduced epithelial surface density suggesting increased pulmonary compliance. These findings show that α and Δ isoforms of CREB1 regulate homeostatic gene expression in the lung and that normal activity of these isoforms is essential to maintain low pulmonary vascular resistance in both normoxic and hypoxic conditions and to maintain the normal alveolar structure. Interventions that enhance the actions of α and Δ isoforms of CREB1 warrant further investigation in hypoxic lung diseases.